Morbimortalidade em esofagectomias: estudo retrospectivo comparativo entre duas técnicas de analgesia pós-operatória - Cunha, Diego da (2018)
Despite the development of anesthesia and analgesia techniques, pain has been a frequent complaint. Acute postoperative pain may cause reflex muscle contraction, immobility, restrictive ventilatory mechanics, accumulation of respiratory secretions, atelectasis, and pneumonia. In addition, pain delays the response to surgical stress, which includes inflammatory, endocrine, and metabolic activation, resulting in catabolic changes, hypercoagulable states, and postoperative organic dysfunction. The influence of analgesia techniques on these events has been extensively investigated. Epidural analgesia has the greatest potential for reduction of postoperative complications and has, indeed, been the most widely investigated technique. Both at the Santa Maria Universitary Hospital and in the literature, thoracic epidural analgesia (TEA) is the gold standard for the treatment of pain following esophagectomy. However, the incidence of postoperative clinical complications and of early mortality is unknown. An observational, analytical, and retrospective study was then conducted to compare TEA with intravenous (IV) analgesia, in which the influence of TEA on the reduction of outcomes such as pneumonia, surgical wound dehiscence, and mortality was hypothesized. A total of 211 medical records were reviewed, of which 203 provided sufficient data for analysis. Patients could be compared in terms of all clinical and demographic characteristics. One hundred eighty-three patients received TEA (Group 1), among whom the incidence of pneumonia (n=41; 22.4%) and of wound dehiscence (n=27; 14.8%) was significantly lower (p<0.001) than among those patients who received IV analgesia (Group 2, n=20). No significant difference was found between the groups regarding the other clinical outcomes. Notwithstanding the small number of patients in this study, it was possible to observe that the incidence of pneumonia and of wound dehiscence was lower in Group 1.